2009
DOI: 10.1007/s10577-009-9096-0
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based cytogenetic profiling reveals recurrent and subtype-associated genomic copy number aberrations in feline sarcomas

Abstract: Injection-site-associated sarcomas (ISAS), commonly arising at the site of routine vaccine administration, afflict as many as 22,000 domestic cats annually in the USA. These tumors are typically more aggressive and prone to recurrence than spontaneous sarcomas (non-ISAS), generally receiving a poorer long-term prognosis and warranting a more aggressive therapeutic approach. Although certain clinical and histological factors are highly suggestive of ISAS, timely diagnosis and optimal clinical management may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…Moreover, some of these chromosomes are syntenic to human chromosome regions already reported as being associated with human breast cancer (e.g., [ 25 , 26 , 27 , 28 , 29 ]). In most of these HBC chromosomes, the observed genomic imbalances were determined via comparative genomic hybridization (CGH), a technology now being applied also in the analysis of cat tumors, but for now only reported in feline sarcomas [ 30 ].…”
Section: “Cytogenomics” Of Cat Mammary Tumorsmentioning
confidence: 99%
“…Moreover, some of these chromosomes are syntenic to human chromosome regions already reported as being associated with human breast cancer (e.g., [ 25 , 26 , 27 , 28 , 29 ]). In most of these HBC chromosomes, the observed genomic imbalances were determined via comparative genomic hybridization (CGH), a technology now being applied also in the analysis of cat tumors, but for now only reported in feline sarcomas [ 30 ].…”
Section: “Cytogenomics” Of Cat Mammary Tumorsmentioning
confidence: 99%
“…38 Kalat et al 28 found, in addition to structural chromosomal aberrations, a chromosomal hyperdiploidy with 40 to 46 chromosomes per cell in feline fibrosarcoma cell lines. An extensive range of genomic imbalances was also shown by Thomas et al, 50 who used a genomic microarray to investigate nonrandom chromosome copy number aberrations in 46 feline sarcomas. A further study of Santos et al analyzed the cat satellite DNA family and telomere sequences by in situ hybridization.…”
mentioning
confidence: 74%
“…Remarkably, combined CGH and FISH analyses showed that a subset of genomic regions exhibited in excess of 30 copies within individual tumor cells, which were distributed across as many as ten different chromosome structures. Also of note, ISS cases showed non-random reorganization of FCA E1 in conjunction with copy number amplification of a discrete region on FCA E1p12 [ 35 ], consistent with the location of a nucleolar organizing region (NOR) [ 36 ]. Elevated argyrophilic nucleolar organizing region (AgNOR) scores, as defined by silver staining analysis, are common indicators of increased cellular proliferation, and have been associated with decreased overall survival for canine soft tissue sarcomas [ 37 ].…”
Section: Injection-site Sarcomamentioning
confidence: 90%
“…Towards this goal, a microarray platform was developed to permit CGH-based identification of recurrent genomic DNA copy number aberrations (CNAs) in feline tumors [ 35 ]. This “aneuploidy array” comprised 210 large-insert clones representing loci anchored at ~15 Mb intervals throughout the initial 2x-coverage cat genome sequence assembly.…”
Section: Injection-site Sarcomamentioning
confidence: 99%
See 1 more Smart Citation